The Influence of Financial Literacy and Islamic Business Ethics on Investment in Islamic Financial Instruments: The Mediating Role of Risk Attitude and the Moderating Role of Religious Knowledge - Dharma, Yulius; Puteh, Anwar; Widodo, Rahmat; Alfaqih, Luqman; Yahya, Aiyub (Journal of Ecohumanism, 2024)
Current challenges in the Islamic banking sector highlight the urgent need to understand the factors influencing ethical and informed investment decisions. This study aims to analyze the impact of financial literacy and Islamic business ethics on investment in Islamic financial instruments, focusing on the mediating role of risk attitude and the moderating role of religious knowledge. Data were collected through a primary method by distributing questionnaires to 300 bank customers and students in Aceh, Indonesia. The model employed is Structural Equation Modeling-Partial Least Squares (SEM-PLS) using Smart PLS software. The findings reveal that financial literacy significantly positively impacts investment decisions and risk attitudes. Islamic business ethics also significantly influence both investment decisions and risk attitudes. Religious knowledge positively affects investment decisions, while risk attitude has a positive impact on investments. However, the moderating effects of risk attitude and religious knowledge on investment are not significant. Risk attitude serves as a crucial mediator in the relationship between financial literacy and investment, as well as between Islamic business ethics and investment. The study underscores the importance of financial literacy, Islamic business ethics, religious knowledge, and risk attitude in shaping investment behavior in the Islamic finance sector, and highlights the need for integrating ethical practices to enhance investment outcomes.